2021
DOI: 10.31234/osf.io/z9c4k
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of Wearing Face Masks While Using Different Speaking Styles in Noise on Speech Intelligibility During the COVID-19 Pandemic

Abstract: The coronavirus pandemic has resulted in recommended/required use of a face mask in public. The use of a face mask compromises communication, especially in the presence of competing noise. It is crucial to measure potential adverse effect(s) of wearing face masks on speech intelligibility in communication contexts where excessive background noise occurs to lead to solutions for this communication challenge. Accordingly, effects of wearing transparent face masks and using clear speech to support better verbal c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 25 publications
0
15
0
2
Order By: Relevance
“…For example, the "Need to allow to see the face" has an important role in the social aspect of sustainability (facilitating comprehension during a conversation and improving safety in certain environments). This requirement is highly debated in the social context; indeed, face masks decrease speech intelligibility and make communication more difficult, especially for people with hearing loss, and few works have been developed to tackle this issue [56][57][58].…”
Section: Mask Development Processmentioning
confidence: 99%
“…For example, the "Need to allow to see the face" has an important role in the social aspect of sustainability (facilitating comprehension during a conversation and improving safety in certain environments). This requirement is highly debated in the social context; indeed, face masks decrease speech intelligibility and make communication more difficult, especially for people with hearing loss, and few works have been developed to tackle this issue [56][57][58].…”
Section: Mask Development Processmentioning
confidence: 99%
“…A study conducted by Altschuler ( 2021 ) found that patients, healthcare providers and caregivers experienced serious communication challenges both within and outside the hospital. The use of a face mask compromises communication, especially in competing noise (Yi et al, 2021 ). Face masks obscure facial expressions and communication and may affect the doctor–patient relationship and overall treatment outcome (Padhy, Rina, & Sarkar 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The adverse effect of face masks on speech comprehension has been investigated in various studies on a behavioural level (Brown et al, 2021;Giovanelli et al, 2021;Rahne et al, 2021;Toscano & Toscano, 2021;Yi et al, 2021). Despite the overall agreement of the adverse effects of face masks on speech comprehension, it has been unclear which features of speech processing are specifically affected.…”
Section: Discussionmentioning
confidence: 99%